Genomic analysis of multidrug-resistant Delftia tsuruhatensis isolated from raw bovine milk - Andriyanov, Pavel A.; Kashina, Daria D.; Menshikova, Alena N. (Frontiers in Microbiology, 2024)
Delftia tsuruhatensis is a gram-negative, aerobic bacterium mostly known as an organic pollutant degrading and growth-promoting microorganism. However, it recently emerged as an opportunistic human pathogen. To date, the source of D. tsuruhatensis infection is not clear. The majority of studies of D. tsuruhatensis have focused on environmental or clinical strains, while investigations of D. tsuruhatensis strains isolated from food sources are limited. In the present study, we report the case of D. tsuruhatensis isolation from raw bovine milk. Classical bacteriology approaches, as well as next-generation sequencing and comparative genomics, were used to characterize the features of the D. tsuruhatensis MR-6/3H strain. The MR-6/3H strain was resistant to 19 antimicrobials among 23 tested, including all aminoglycosides, phenicol, trimethoprim-sulfamethoxazole, and almost all β-lactams. Phylogenetically, the MR-6/3H was close to clinical origin strains, including those previously isolated in Russia. Comparative genomics revealed the presence of putative antimicrobial resistance genes in the MR-6/3H isolate, mostly associated with efflux systems. Notably, genus-specific OXA-926-like β-lactamase was also detected. In all, 27 putative virulence factors were predicted, the majority of which were associated with motility, adherence, stress survival, siderophore synthesis, and immunomodulation. In the MR-6/3H genome, the five prophage regions were identified, including two with intact levels. Integrons and CRISPR-Cas systems were not detected in the MR-6/3H isolate. Thus, our findings suggest that raw milk can be the potential source of and transmission route for the dissemination of multidrug-resistant D. tsuruhatensis.